Approche comparative des colles d’algues Funori et JunFunori® - Anne-Cécile Dauchez (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Comparative study between glues produced out of seaweeds, Funoris and JunFunori®, with glues used regularly in conservation treatments. The comparison concernes at first pure glues then secondly, fillings applied to MDF (medium density fiberboard).